WOMEN TAKING UP SPACE: A CONCEPTUAL ANALYSIS OF THE GENDER-DIGITAL DIVIDE IN SOUTH AFRICA (Proceedings of the International Conference on Social Sciences, 2023)
The world has become progressively digital and visibility into the digital gender gap is becoming crucial. Each year, data demonstrates a persistent gender divide in access to information and resources that promote economic and social mobility. According to a study by Women in Digital Transformation, the COVID-19 pandemic exacerbated the gender digital divide. Sub-Saharan Africa appears to be following the continental trend of low digital connectedness among women with approximately 300 million unconnected women living in the region. In South Africa, the gender gap in digital technology access, use, and adoption remains persistent. Ultimately, gaps in digital skills, employment, and entrepreneurship in Information Communication Technology and other sectors result from this inequality in access. Utilizing a conceptual research design, this paper primarily sought to ascertain the gender discrepancies that still exist regarding access to digital resources and knowledge, despite women empowerment being one of the key sustainable development goals for 2030. A theoretical framework encompassing the theory of the digital divide, within the greater communication theory was used to interrogate the identified phenomena in this study. The paper further offered a conceptual framework, identified by the authors as being the best practices for bridging the gaps on the subject. A further empirical enquiry is recommended to support the conceptual insights inferred in this study.
Keywords: gender digital divide; women; 4IR; sustainable development; South Africa